Evolution and Features of China’s Central Government Funding System for Basic Research - Bai, Aruhan; Wu, Cong; Yang, Kejia (Frontiers in Research Metrics and Analytics, 2021)
Basic research is believed to be a crucial factor for building national innovation capacity and therefore was perceived as a key battleground for national technological and economic competition. Since the economic reform and opening up in the late 1970s, China has made great achievements in building up its national research system. However, the lacking capabilities to conduct ground-breaking scientific work remain one of the daunting challenges for the country. How to restructure its funding system for basic research so that to reinvigorate its indigenous innovation capacity has been one of the main concerns for the Chinese government in recent years. To address this, the paper proposes a conceptual framework to analyse how China’s central government funding system for basic research has evolved since 1985. The paper concludes with a discussion of the identified problems and challenges that China is facing in its current funding system for basic research.